Association between chronic hepatitis C virus infection and low muscle mass in US adults. Issue 12 (2nd July 2014) - Gowda, C.; Compher, C.; Amorosa, V. K.; Lo Re, V.
Summary Given that low muscle mass can lead to worse health outcomes in patients with chronic infections, we assessed whether chronic hepatitis C virus (HCV) infection was associated with low muscle mass among US adults. We performed a cross‐sectional study of the National Health Examination and Nutrition Study (1999–2010). Chronic HCV‐infected patients had detectable HCV RNA. Low muscle mass was defined as <10th percentile for mid‐upper arm circumference (MUAC). Multivariable logistic regression was used to determine adjusted odds ratios (aORs) with 95% confidence intervals (CIs) of low muscle mass associated with chronic HCV. Among 18 513 adults, chronic HCV‐infected patients (n = 303) had a higher prevalence of low muscle mass than uninfected persons (13.8% vs 6.7%; aOR, 2.22; 95% CI, 1.39–3.56), and this association remained when analyses were repeated among persons without significant liver fibrosis (aOR, 2.12; 95% CI, 1.30–3.47). This study demonstrates that chronic HCV infection is associated with low muscle mass, as assessed by MUAC measurements, even in the absence of advanced liver disease.